Data to the growth of yoy (0+) tenches (Tinca tinca L.) in Tisza Lake - Harka, Ákos; Sály, Péter; Antal, László (Acta Agraria Debreceniensis, 2007)
Young of the year (YOY) tenches (Tinca tinca L.) were caught in relatively great number in Tisza-Lake at the Tiszafüred section on last days of October in 2004. The standard length of these fishes varied between 20 and 46 mm. It seemed that the collected sample could provide appropriate data to examine the size-structure of YOY tenches, so we measured their standard body-lengths in mm and -weights in hundred parts of gramm unit. After the statistical analysis were found the follows: 1. The curve of length frequency corresponds with normal distribution, i.e. there was not found multimodal curve as could be expected in the case of a periodic spawning species. 2. The average standard length of the examined individuals – although the environmental conditions of the population is good – was only 31 mm. It is far below the 37 mm average of the lowest growth of tench population was found in the scientificpapers. 3. More than 20% of measured sample belonged to the range of 20-26 mm. The estimated ages of these fish specimens are about 70 days, according the scientificpapers. By right of above mentioned can be concluded that the sample represents only one age-group from a late spawning, and not the whole range of YOY tenches, so these data can give information about the size structure only of this group. The 31 mm average standard length of individuals, origin from spawning in late July or beginning of August is accordance with age and environmental conditions as well.